Estimation of operational value-at-risk in the presence of minimum collection threshold: An empirical study - Anna Chernobai; Christian Menn; Svetlozar T. Rachev; Stefan Trück (Karlsruher Institut für Technologie (KIT), Institut für Volkswirtschaftslehre (ECON), 2010)
The recently finalized Basel II Capital Accord requires banks to adopt a procedure to estimate the operational risk capital charge. Under the Advanced Measurement Approaches, that are currently mandated for all large internationally active US banks, require the use of historic operational loss data. Operational loss databases are typically subject to a minimum recording threshold of roughly 10,000. We demonstrate that ignoring such thresholds leads to biases in corresponding parameter estimates when the threshold is ignored. Using publicly available operational loss data, we analyze the effects of model misspecification on resulting expected loss, Value-at-Risk, and Conditional Value-at-Risk figures and show that underestimation of the regulatory capital is a consequence of such model error. The choice of an adequate loss distribution is conducted via in-sample goodness-of-fit procedures and backtesting, using both classical and robust methodologies.
urn:nbn:de:swb:90-197730
Keywords: 330; Bankrisiko; Operationelles Risiko; Risikomaß; Schätzung; Internationale Bank; USA